2019
DOI: 10.1017/s0022215119001725
|View full text |Cite
|
Sign up to set email alerts
|

Elective neck dissection for the node-negative neck during salvage laryngectomy: an analysis of survival outcomes and complication rates

Abstract: ObjectivesThis study aimed to evaluate the effect of neck dissection on survival and complication rates in patients with no clinical or radiological evidence of cervical nodal disease (N0) undergoing salvage laryngectomy.MethodsA retrospective study was conducted of patients with squamous cell carcinoma of the larynx following primary radiotherapy that required salvage laryngectomy. Disease-free and overall survival rates were compared over three years using Kaplan–Meier analysis. Pharyngocutaneous fistula rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A 2020 meta-analysis showed a relative risk of disease-specific mortality of 1.04 (95% CI, 0.83-1.3) between END and observation. The decision to perform an END at the time of salvage TL may also be associated with morbidity secondary to increased postoperative complication and fistula rates . Additionally, if an END is performed, there is little guidance to support which nodal stations to dissect in an irradiated field, warranting further investigation …”
Section: Introductionmentioning
confidence: 99%
“…A 2020 meta-analysis showed a relative risk of disease-specific mortality of 1.04 (95% CI, 0.83-1.3) between END and observation. The decision to perform an END at the time of salvage TL may also be associated with morbidity secondary to increased postoperative complication and fistula rates . Additionally, if an END is performed, there is little guidance to support which nodal stations to dissect in an irradiated field, warranting further investigation …”
Section: Introductionmentioning
confidence: 99%
“…Gouzos et al looked at the 3‐year outcomes for salvage laryngectomy patients with no clinical or radiological evidence of cervical nodal disease and found no significant difference in survival outcomes or post‐operative complications based on extent of nodal surgery 10 . This has been replicated in a meta‐analysis also showing no significant difference of overall survival at 5 years in patients in the salvage laryngectomy setting against patients whose necks were observed 3 .…”
Section: Discussionmentioning
confidence: 98%
“…Brazilian group (n = 272) who analysed the issue of contralateral neck disease in the salvage laryngectomy setting also found low rates of occult disease (3.5%), with a higher risk associated with supraglottic primary sites, mainly involving level II and level III nodes 9. Gouzos et al looked at the 3-year outcomes for salvage laryngectomy patients with no clinical or radiological evidence of cervical nodal disease and found no significant difference in survival outcomes or post-operative complications based on extent of nodal surgery 10. This has been replicated in a meta-analysis also showing no significant difference of overall survival at 5 years in patients Overall survival and disease-specific survival of salvage laryngectomy patients Nodal staging based on anatomical position of the tumour…”
mentioning
confidence: 98%
“…7-10 Many authors have shown low yield of positive lymph nodes, higher complication rates, and ultimately no improvement in regional control or survival outcomes. 10-14 Still, some authors who have shown a higher rate of nodal metastasis or survival benefit advocate for neck dissection in the salvage setting either routinely or in selected cases. 10,15-17 These studies are based on single institution experiences and are limited by small patient numbers.…”
Section: Introductionmentioning
confidence: 99%